1986
DOI: 10.1111/j.1440-0960.1986.tb00302.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Haematinic Deficiencies in Patients With Recurrent Aphthous Stomatitis

Abstract: r SUMMARY To resolve the conflict among published reports as to the value of screening for haematinic deficiencies in patients with recurrent aphthous stomatitis, we evaluated 102 such patients. Venous blood was sampled for a complete blood cell count and measurements of serum iron, serum iron-binding capacity and capacity saturation, serum folate, and serum vitamin BM. Of the 40 patients deficient In iron or folate, 6 were anaemic, 23 were deficient in iron, and 22 were deficient in folate; 5 were deficient i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 11 publications
2
12
2
Order By: Relevance
“…Haematinic (iron, folic acid or vitamin B 12 ) deficiencies may be twice as common in some groups of patients with RAS as in healthy control subjects (Wray et al , 1975; Challacombe et al , 1977a, 1983; Hutcheon et al , 1978; Tyldesley, 1983; Rogers and Hutton, 1986; Field et al , 1987; Porter et al , 1988). About 20% of patients with RAS may have a haematinic deficiency, although one US study did not report any haematinic problem (Olson et al , 1982).…”
Section: Systemic Factors Predisposing To Rasmentioning
confidence: 99%
See 1 more Smart Citation
“…Haematinic (iron, folic acid or vitamin B 12 ) deficiencies may be twice as common in some groups of patients with RAS as in healthy control subjects (Wray et al , 1975; Challacombe et al , 1977a, 1983; Hutcheon et al , 1978; Tyldesley, 1983; Rogers and Hutton, 1986; Field et al , 1987; Porter et al , 1988). About 20% of patients with RAS may have a haematinic deficiency, although one US study did not report any haematinic problem (Olson et al , 1982).…”
Section: Systemic Factors Predisposing To Rasmentioning
confidence: 99%
“…RAS-like ulceration can occur in Behcet's disease, however patients with the latter have multisystem disease, particularly affecting (Mittal et al, 1985;Schreiner and Jorizzo, 1987;Arbesfeld and Kurban, 1988;Jankowski et al, 1992;Stratigos et al, 1992). Haematinic (iron, folic acid or vitamin B 12 ) deficiencies may be twice as common in some groups of patients with RAS as in healthy control subjects (Wray et al, 1975;Challacombe et al, 1977aChallacombe et al, , 1983Hutcheon et al, 1978;Tyldesley, 1983;Rogers and Hutton, 1986;Field et al, 1987;Porter et al, 1988). About 20% of patients with RAS may have a haematinic deficiency, although one US study did not report any haematinic problem (Olson et al, 1982).…”
Section: Systemic Factors Predisposing To Rasmentioning
confidence: 99%
“…In several studies, hematinic (iron, folic acid, or vitamin B 1 2) deficiencies have been demonstrated to be twice as common in RAS patients than in controls (Wray et al, 1975;Challacombe et al, 1977aChallacombe et al, , 1983Hutcheon et al, 1978;Tyldesley, 1983;Rogers and Hutton, 1986;Field et al, 1987;Porter et al, 1988). About 20% of patients with RAS may have a hematinic deficiency, though one US study did not report any hematinic problem (Olsen et al, 1982).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Individuals with RAS possibly related to foodstuffs may occasionally benefit from dietary alterations (Spouge and Diamond, 1963;Eversole et al, 1983;Hay and Reade, 1984), while hematinic replacement can be of value in patients with hematinic deficiency of unknown cause (Wray et al, 1975;Rogers and Hutton, 1986;Porter et al, 1992a). Zinc sulphate therapy is not effective (Wray, 1982).…”
Section: Management (A) Diagnosismentioning
confidence: 99%
“…Of the 75 patients, 66% had RAU lesions of the more severe herpetiform or major types. Estimates in the literature from before the advent of the AIDS epidemic suggest that minor RAU comprised about 80% of all cases, whereas major and herpetiform RAU together comprised only about 20% (Lehner 1977;Greenspan, 1983;Rogers and Hutton, 1986;Hutton and Rogers, 1987). Given that the OAC Clinic specializes in unusual oral problems, seeing persons with severe RAU is not unexpected.…”
Section: Introductionmentioning
confidence: 99%